Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

An infinitesimal $SO(N)$ transformation matrix can be written :

$$R_{ij} = \delta_{ij}+\theta_{ij}+O(\theta^2)$$

Now it has to be shown that $\theta_{ij}$ is real and anti-symmetric.

I've started with the orthogonality condition like following:

$$R^TR=\boldsymbol 1$$ $$\implies (R^TR)_{ij}=\delta_{ij}$$ $$\implies \sum_kR^T_{ik}R_{jk}=\delta_{ij}$$ $$\implies \sum_kR_{ik}R_{jk}=\delta_{ij}$$ $$\implies \sum_kR_{ik}R_{ik}=\delta_{ii}$$ $$\implies \sum_jR_{ij}R_{ij}=1$$

Now i can stick my infinitesimal form of $R_{ij} $ into the above formula:

$$\sum_j(\delta_{ij}+\theta_{ij}+O(\theta^2))(\delta_{ij}+\theta_{ij}+O(\theta^2))=1$$ $$\implies \sum_j (\delta_{ij}\delta_{ij}+2\theta_{ij}\delta_{ij}+O(\theta^2))=1$$

As you can easily see my calculations are going nowhere.

share|cite|improve this question

migrated from Jun 17 '13 at 2:31

This question came from our site for active researchers, academics and students of physics.

You are on the right track. Note that ${}^t \theta_{ij} = \theta_{ji}$ and please be careful with (dummy) indices. You should never write anything like $\delta_{ii}$ in a covariant calculation. – Vibert Jun 15 '13 at 19:47
up vote 2 down vote accepted



Now in the last sum you wrote, you get a different result,


This is true, if $\theta_{ij}=-\theta_{ji}$. To prove that $\theta_{ij}$ is real, evaluate this $\mathrm{Im}[(R^{T}R)_{ij}]$. You will find that $\mathrm{Im}[(R^{T}R)_{ij}]=0$.

share|cite|improve this answer
I don't fully agree with the calculation. Why repeat the index $i$ twice but sum over $j$ explicitly? It's much cleaner to write $$(R \cdot {}^tR)_{ik} = (\delta_{ij} + \theta_{ij})(\delta_{jk} + \theta_{kj}) = \delta_{ik} + (\theta_{ik} + \theta_{ki}) + \mathrm{O}(\theta^2)$$ to reach the desired conclusion. – Vibert Jun 15 '13 at 21:08
Yes I know (personally I don't like to write in this manner), but I wanted to keep the same notation as the OP used. – Leonida Jun 15 '13 at 21:12

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.